Essential Oils (The East and Central African Journal of Pharmaceutical Sciences, 2020)
Essential oils are the backbone of perfume, soap and spice industries. They constitute the main ingredients in aromatherapy. These oils are of interest today because of the trend back to natural drugs and therapies in medicine popularly known as naturopathy.
Keywords: Essential oil, Research, Aromatherapy